Influence of Pt Addition and Manufacturing Process on the Failure Mechanisms of NiCoCrAlYTa-Base Thermal Barrier Coating Systems under Thermal Cycling Conditions - Aurelie Vande Put; Djar Oquab; Aymeric Raffaitin; Daniel Monceau (Metals, 2018)
The cyclic oxidation of NiCoCrAlYTa-base thermal barrier coating systems was investigated at 1100 °C. The influence of the NiCoCrAlYTa deposition process, the coating modification by a Pt-overlayer, and the surface preparation steps were studied. Thermal cycling results showed that the addition of a Pt-overlayer, a dense and oxide-free bond-coating microstructure, together with a smooth NiCoCrAlYTa surface prior to Pt deposition and a suitable surface preparation before thermal barrier deposition all increase the lifetime. Degradation mechanisms are proposed to explain how coating defects develop during thermal cycling and how the fabrication process influences both failure and lifetime.